2015
DOI: 10.3390/su8010036
|View full text |Cite
|
Sign up to set email alerts
|

Social Science in Forestry Curricula: A Case Study of Colombia Forestry Programs

Abstract: Abstract:Tropical forest management depends greatly on complex social interactions. To understand the underlying human causes of deforestation and to plan forest management, it is of great importance to incorporate social science in the study of forestry. There is insufficient information about the incorporation of social sciences in undergraduate forestry programs. Foresters are well prepared in ecology, silviculture, forest measurements, and operational topics such as logging, but their knowledge of basic el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous studies analyzing the undergraduate forestry curriculum [3,4] concluded that social sciences are not well represented. Yet social sciences seem well represented in Turkish forestry program curricula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies analyzing the undergraduate forestry curriculum [3,4] concluded that social sciences are not well represented. Yet social sciences seem well represented in Turkish forestry program curricula.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies on the assessment of forestry education and curricula. Forestry programs curricula in Colombia were assessed for their inclusion of social sciences [3]. Undergraduate curricula of Society of American Foresters (SAF) accredited forest programs in the USA were examined for their deficiencies of social sciences [4].…”
Section: Introductionmentioning
confidence: 99%
“…Generic competences have been recognized as insufficient for some time (Sample et al 2015;Rekola et al, 2017;Rekola et al, 2018;Villarraga-Florez, Rodríguez-Pineros and Martínez-Cortés, 2016;Lee et al, 2011). The results of this study suggest that some improvement has occurred in this area; however, generic competences are still at insufficient levels.…”
Section: University and College Levelmentioning
confidence: 99%
“…Studies across economies focus on Europe [20,29], and Brazil, China, and Finland [30]. Recent literature addresses new topics, including online forestry education [31][32][33], students' views on forestry education or participatory curricula development [30,34,35], internationalization of forestry education [2,36], social science in forestry education [37], declining enrolment in forestry education [38], women in forestry higher education [39], forestry higher education outcomes [40], and colonial legacies in forestry higher education [41].…”
Section: The Forestry Higher Education and Forestry Continuing Education Debatesmentioning
confidence: 99%